Electric Moms and Quad Drivers: People with Disabilities Buying, Making, and Using Technology in Postwar America - Williamson, Bess (American Studies, 2012)
In the decades following World War II, an increasing number of Americans survived injury and illness to live long and active lives with physical disabilities. Despite improved medical prospects, they faced significant barriers in the everyday design of products, houses and streetscapes. In an era before the advent of a disability rights movement, I argue, people with disabilities made their own access by selecting and altering everyday technologies, tinkering their way to improved personal mobility and greater inclusion in everyday American life. Their efforts foreshadowed the disability rights movement’s call for public accommodations in the 1970s and beyond.